Measurement of the ratio of branching fractions B(B-0 -> K*(0)gamma)/B(B-s(0) -> phi gamma) - Aaij, R; Abellan Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Alkhazov, G; Alvarez Cartelle, P; et al. (2012)
The ratio of branching fractions of the radiative B decays B0→K *0γ and B0s→φγ has been measured using 0.37fb -1 of pp collisions at a center of mass energy of √s=7TeV, collected by the LHCb experiment. The value obtained is B(B0→K *0γ)B(B0s→φγ)=1.12±0.08- 0.04-0.08+0.06+0.09, where the first uncertainty is statistical, the second systematic, and the third is associated with the ratio of fragmentation fractions f s/f d. Using the world average for B(B0→K *0γ)=(4.33±0.15)×10 -5, the branching fraction B(B0s→φγ) is measured to be (3.9±0.5)×10 -5, which is the most precise measurement to date. © 2012 CERN.